Analisis Kadar Residu Derifat Formalin Dalam Galon Isi Ulang yang Beredar di Daya, Makassar, Sulawesi Selatan - Jeni Anti Barrang; Bela Chintya; Arianty Kurniastuty; Astuti Amin; Lukman Muslimin (Jurnal Farmasi dan Ilmu Pengobatan, 2018)
Using gallons as a main source of drinking water are increasing. Gallon packs are composed of plastic polymers that will decompose in sunlight exposure. This study aims to analyze the levels of formaldehyde residues in refill circulating in the Daya, Makassar, South Sulawesi. Formalin residues are determined by Schiff’s reagent. The results showed that 7 from 12 gallon contained formalin derivatives with a serius level (16.45 µg/mL).